Comparison of the capacity of different viral internal ribosome entry segments to direct translation initiation in poly(A)-dependent reticulocyte lysates - Paulous, Sylvie (Oxford University Press, 2003)
Polyadenylation stimulates translation of capped eukaryotic mRNAs and those carrying picornaviral internal ribosome entry segments (IRESes) in vivo. Rabbit reticulocyte lysates (RRL) reproduce poly(A)-mediated translation stimulation in vitro after partial depletion of ribosomes and ribosome-associated factors. Here, we have evaluated the effects of varying different parameters (extent of extract depletion, cleavage of eIF4G, concentrations of KCl, MgCl(2) and programming mRNA) on IRES-driven translation efficiency and poly(A)-dependency in ribosome-depleted RRL. For comparison, the study included a standard capped, polyadenylated mRNA. Dramatic differences were observed in the abilities of the different IRESes to direct translation in ribosome-depleted extracts. While the hepatitis A virus IRES was incapable of driving translation in physiological conditions in depleted RRL, mRNAs carrying the foot-and-mouth disease virus and hepatitis C virus IRESes were translated significantly better than a standard cellular mRNA in the same conditions. Indeed, the capacities of these IRESes to direct translation in ribosome-depleted RRL were similar to those reported previously in certain cell lines. Both the abilities of the IRESes to drive translation and their individual salt optima in ribosome-depleted extracts suggest that these elements have dramatically different affinities for some component(s) of the canonical translation machinery. Finally, using poliovirus as an example, we show that the ribosome-depleted system is well suited to the study of the translational capacity of naturally occurring IRES variants.